Cranial morphology, quality of breastfeeding and gender in newborns of breasfeeding mothers (Research, Society and Development, 2023)
At the end of gestation, the cranial sutures are still not completely fused, being liable to be misaligned by mechanical forces, generating cranial alterations. Consequently, these cranial alterations can lead to a deficit in breastfeeding, causing damage to the development of the newborn. The aim of this study is to investigate whether there are associations between the type of delivery, the sex of the newborn and the quality of breastfeeding on the cranial morphology of newborns in a maternal-infant ward of a University Hospital in Western Paraná. Newborns were evaluated between 24 and 48 hours, where an interview was conducted with the mother and later the LATCH and craniometry of newborns were evaluated, in order to determine the quality of breastfeeding and cranial morphology. A total of 66 newborns participated in the study, of which 25 were excluded. Of the sample used for the study, the predominance was male (53.7%), with an average weight of 3.2 kg, length of 48.6 cm, average age of mothers 26.2 years and average gestational age of 38.7 weeks. The predominant type of delivery was cesarean section (65.9%) and the vast majority of newborns had some cranial alteration (87.8%), the mean total LATCH was 7.66. It is concluded that there was no association between the mode of delivery and the presence of cranial alterations, the results indicate a high rate of newborns with cranial alterations, however there was no statistically significant difference in the LATCH of newborns with normal cranial morphology for those with cranial alterations.